Efektifitas Penginduksi Resistensi dan Biopestisida terhadap Penyakit Bercak Daun Cercospora dan Antraknosa pada Cabai (Capsicum annuum L.) - Isnawan, Bambang Heri; Mubarok, Khusnul (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2014)
A research to confirm potential natural resources as an induced systemic resistance agent and bio- pesticide and it combination against Cercospora leaf spot and anthracnose on pepper. The research method was conducted by experiment on field, arranged in factorial design 3 x 5, arranged Randomized Completely Block Design with three replications as blocks. The First factor was inducer of resistance, consist of 3 levels i.e. non-inducer of resistance, inducer of resistance by Mirabilis jalapa and inducer of resistance by Amaranthus spinosus. The Second factor was bio-pesticide consist of 5 level i.e. non-bio-pesticide, bio-pesticide Amp, bio-pesticide Pfm001, bio-pesticide Amp+Pfm001 and chemical fungicide. The result of this research showed that inducer of resistance could suppressing damage fruit by anthracnose but could not influencing in Cercospora leafspot. Inducer of resistance could not be influencing growth of plant but could suppressing damage fruit volume and total damage fruit. Inducer of resistance i.e. Mirabilis jalapa and Amaranthus spinosus could suppressing damage fruit by anthracnose. Bio-pesticide could not be influencing in Cercospora leafspot but could suppressing anthracnose on pepper. Bio-pesticide could not be influencing the growth of pepper but could suppressing total damage fruit and damage fruit volume also increasing up the yield. There is no interaction between inducer of resistance and bio-pesticide through every parameter except for the area under diseases progress curve (AUDPC).